Keragaman Jenis Zooplankton Di Perairan Waduk Mulur Kabupaten Sukoharjo Provinsi Jawa Tengah - Wulandari, Vidia, Efri Roziaty, S. Si., M. Si (2017)
DIVERSITY TYPES OF ZOOPLANKTON IN MULUR STORAGE RESERVIOR WATERS IN SUKOHARJO OF CENTRAL JAVA ABSTRACT The Research is about diversity of zooplankton species in Mulur Storage Reservoir Waters in Sukoharjo of Central Java. It has been implemented on March until April 2017. The purpose of this study is to determine the diversity of zooplankton species. This Research was using quantitative explorative research. The method is used a purposive sampling and establish 3 stations, such as Station A (fishing cages), Station B (fishing area), and Station C (field irrigation). The result of Zooplankton diversity found 24 species of 7 main phylum, it names Protozoa (5 species), Chaetognatha (1 species), Sarcomatigophora (5 species), Rotifera (7 species), Ciliophora (3 species), Athropoda (2 species), and Apicomplexa (1 species). Index diversity (H') ranges from -2.81 to -2.81, it means an unstable biota community. The result indicates that Mulur Storage Reservoir Waters in Sukoharjo of Central Java needs more attention in order to the zooplankton community can be stable by reducing environment pollution. Keywords : diversity, protozoa, mulur storage reservior, zooplankton.